Respuesta :

Answer:

[tex]=2xy+6x^2-6x[/tex]

Step-by-step explanation:

[tex]-2x\left(-y-3x+3\right)\\\mathrm{Distribute\:parentheses}\\=\left(-2x\right)\left(-y\right)+\left(-2x\right)\left(-3x\right)+\left(-2x\right)\cdot \:3\\\mathrm{Apply\:minus-plus\:rules}\\\left(-a\right)\left(-b\right)=ab,\:\:+\left(-a\right)=-a\\=2xy+2\cdot \:3xx-2\cdot \:3x\\\mathrm{Simplify}\:2xy+2\cdot \:3xx-2\cdot \:3x:\quad 2xy+6x^2-6x\\2xy+2\cdot \:3xx-2\cdot \:3x\\2\cdot \:3xx=6x^2\\2\cdot \:3x=6x\\=2xy+6x^2-6x[/tex]

please see the attached picture for full solution

Hope it helps

Good luck on your assignment

Ver imagen TheAnimeGirl